Non-Pharmacological Therapy of Red Ginger Hugging Pillows (Baper) to Reduce Dysmenorrhea in Adolescents - Selvi Puspan Sari; Ririn Anggriani Sitorus (GLOBAL HEALTH SCIENCE GROUP, 2026)
In Indonesia, the prevalence of dysmenorrhea reaches 60 to 70%, with three-quarters of the number of adolescents experiencing mild to severe pain and as many as 7-15% do not go to school. The incidence of dysmenorrhea in Indonesia is around 54.89% primary dysmenorrhea, the remaining 45.11% secondary dysmenorrhea. Adolescents who experience dysmenorrhea tend to reduce their activities, especially activities at school and often decide not to go to school. Pharmacological therapy that is too frequent can cause several side effects such as stomach irritation, intestinal colic, diarrhea and asthma attacks. Non-Pharmacological Therapy is an alternative for dysmenorrhea, one of which is the red ginger hug pillow (BAPER). Red ginger is an option because it contains a lot of oleoresin, a bioactive component consisting of gingerol and shogaol which works as an anti-inflammatory and provides a warming effect so that prostaglandins can be blocked and reduce the intensity of pain during menstruation. This type of research uses a quasi-experimental research design with a pretest posttest control group design. In early September 2025, researchers began collecting data on dysmenorrhea history from students at SMA Negeri 2 Kisaran. They were assisted by homeroom teachers and OBGYN doctors to better understand the students' condition. They also conducted interviews with both students and homeroom teachers. During this data collection phase, 60 students with a history of dysmenorrhea were identified. The sampling technique used was purposive sampling with a sample of 60 middle-aged adolescents (aged 15-17 years) at SMAN 2 Kisaran. The statistical test results obtained a P value = 0.000 < 0.05, so it can be concluded that non-pharmacological therapy of red ginger hug pillows can reduce dysmenorrhea. Red ginger hug pillows (BAPER) can be a solution for adolescents who experience dysmenorrhea.